Transient expression of Human papillomavirus type 16 L2 epitope fused to N- and C-terminus of coat protein of Potato virus X in plants - Cerovska, Noemi; Hoffmeisterova, Hana; Moravec, Tomas; Plchova, Helena; Folwarczna, Jitka; Synkova, Helena; Ryslava, Helena; Ludvikova, Viera; Smahel, Michal (Journal of biosciences, 2012)
Transient expression of foreign genes based on plant viral vectors is a suitable system for the production of relevant immunogens that can be used for the development of a new generation of vaccines against a variety of infectious diseases. In the present study the epitope derived from HPV-16 L2 minor capsid protein (amino acids 108-120) was expressed from Potato virus X (PVX)-based vector pGR106 as N- or C-terminal fusion with the PVX coat protein (PVX CP) in transgenic Nicotiana benthamiana plants. The fusion protein L2 108-120-PVX CP was successfully expressed in plants at a level of 170 mg/kg of fresh leaf tissue. The C-terminal fusion protein PVX CP- L2 108-120 was expressed using mutated vector sequence to avoid homologous recombination at a level of 8 mg/kg of fresh leaf tissue. Immunogenicity of L2 108-120-PVX CP virus-like particles was tested after immunization of mice by subcutaneous injection or tattoo administration. In animal sera the antibodies against the PVX CP and the L2 108-120 epitope were found after both methods of vaccine delivery.
Keywords: Electrophoresis, Polyacrylamide Gel; imunizace; Plant Leaves; Nicotiana; Epitopes; Humans; Recombinant Fusion Proteins; genetické vektory; elektroforéza v polyakrylamidovém gelu; klonování DNA; geneticky modifikované rostliny; onkogenní proteiny virové; Female; virion; Blotting, Western; ELISA; Capsid Proteins; lidé; zvířata; myši; Oncogene Proteins, Viral; listy rostlin; myši inbrední C57BL; Enzyme-Linked Immunosorbent Assay; Mice; ženské pohlaví; Plants, Genetically Modified; Virion; tabák; Mice, Inbred C57BL; rekombinantní fúzní proteiny; virové plášťové proteiny; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; protilátky virové; Genetic Vectors; Antibodies, Viral; Animals; western blotting; epitopy; oligonukleotidy; Cloning, Molecular; Immunization; Oligonucleotides